2005
DOI: 10.1007/s10067-005-0103-3
|View full text |Cite
|
Sign up to set email alerts
|

Hypermobility syndrome increases the risk for low bone mass

Abstract: Few studies on the benign joint hypermobility syndrome suggest a tendency toward osteopenia, but there are conflicting results. We assessed bone mineral density in pre-menopausal women with hypermobility. Twenty-five consecutive Caucasian women diagnosed with benign hypermobility syndrome by Beighton score and 23 age- and sex-matched controls were included in the study. Age, menarch age, number of pregnancies, duration of lactation, physical activity and calcium intake were questioned according to European Ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
1

Year Published

2010
2010
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(25 citation statements)
references
References 20 publications
0
20
1
Order By: Relevance
“…The percentage of subjects reporting musculoskeletal complaints was much lower in our sample of subjects with JHS, which may be because our sample was taken from a healthy population rather than a JHS specialty clinic. The increased prevalence of stress fractures among subjects with JHS in the current study was not expected, although prior studies have shown decreased bone density in GJH [43].…”
Section: Discussioncontrasting
confidence: 58%
“…The percentage of subjects reporting musculoskeletal complaints was much lower in our sample of subjects with JHS, which may be because our sample was taken from a healthy population rather than a JHS specialty clinic. The increased prevalence of stress fractures among subjects with JHS in the current study was not expected, although prior studies have shown decreased bone density in GJH [43].…”
Section: Discussioncontrasting
confidence: 58%
“…survey [ (Gharbiya et al, 2012], baseline coagulation tests [Jackson et al, 2013] and bone mineral density test [Gulbahar et al, 2006]. A few patients also needed a head-up tilt-test [Mathias et al, 2011].…”
Section: Methodsmentioning
confidence: 99%
“…Some studies confirm that JHS can produce rheumatologic complications such as premature osteoarthrosis, calcium pyrophosphate crystal deposition, and chondrocalcinosis [13][14][15]. Other studies show an association between JHS and fibromyalgia, with the prevalence of JHS in patients with fibromyalgia ranging between 25% [16•] and 27% [17].…”
Section: Introductionmentioning
confidence: 94%